2016
DOI: 10.1007/s11886-016-0747-4
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Ablation as First-Line Therapy for Atrial Fibrillation: Ready for Prime-Time?

Abstract: Current guidelines include atrial fibrillation (AF) catheter ablation as part of the management strategy in patients that have failed at least one oral antiarrhythmic drug treatment course. However, growing evidence derived from both randomized and non-randomized studies demonstrate lower rates of AF recurrence and AF burden in patients with paroxysmal AF that are naïve to antiarrhythmic drug treatment. Furthermore, progression from paroxysmal AF to persistent AF appears to be delayed by early catheter ablatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…1 However, growing evidence has shown lower rates of AF recurrence and AF burden in patients with paroxysmal AF that were submitted to ablation as a first-line therapy option. 2 In addition to that, progression from paroxysmal AF to persistent AF appears to be delayed by early catheter ablation of AF. 2 Therefore, catheter ablation has been increasingly considered as a first-line therapy option, which makes it more important to use screening factors to closely follow patients with higher risk of AF recurrence and post-procedural complications.…”
Section: Introductionmentioning
confidence: 99%
“…1 However, growing evidence has shown lower rates of AF recurrence and AF burden in patients with paroxysmal AF that were submitted to ablation as a first-line therapy option. 2 In addition to that, progression from paroxysmal AF to persistent AF appears to be delayed by early catheter ablation of AF. 2 Therefore, catheter ablation has been increasingly considered as a first-line therapy option, which makes it more important to use screening factors to closely follow patients with higher risk of AF recurrence and post-procedural complications.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that fibrotic tissue correlates with regions of low voltage ( Jadidi et al, 2013 ; Rodríguez-Mañero et al, 2018 ; Caixal et al, 2020 ). Beyond pulmonary vein isolation, these low voltage regions are commonly targeted by ablation ( Nielsen et al, 2014 ; Carrizo and Morillo, 2016 ; Schade et al, 2020 ). A drawback of the low voltage guided approach is that it ignores the rate-dependent nature, i.e., restitution information, of both amplitude and CV.…”
Section: Introductionmentioning
confidence: 99%